Correlation of beta-globin haplotypes with the clinical complications and alterations in circulating hematopoietic stem and progenitor cells with the use of hydroxyurea in sickle cell anemia - Lima, Jonathan Milhomens dos Santos (2024)
Sickle cell anemia (SCA) is a hereditary disorder characterized by abnormal hemoglobin production, leading to the formation of sickle-shaped red blood cells. This genetic mutation in the beta-globin gene results in a single amino acid replacement (valine instead of glutamic acid) in the hemoglobin protein. Hematopoietic stem cells give rise to red blood cells with this sickle cell mutation, leading to clinical complications such as acute and chronic pain, anemia, increased infection risk, stroke, organ damage, and reduced life expectancy. Sickle cell disease (SCD) poses significant clinical challenges, emphasizing the need for early diagnosis and monitoring healthcare. In this study, we assessed the β-globin gene haplotypes in a Brazilian cohort of 327 SCD patients from South, Midwest, and Southeast regions. Employing a single-nucleotide polymorphisms (SNP) multiplex system, we simultaneously analyzed nine SNPs defining Central African Republic (CAR), Benin (BEN), Senegal (SEN), and Cameroon (CAM) hemoglobin beta sickle (HBBS) gene haplotypes. Additionally, we evaluated the impact of hydroxyurea (HU), a primary treatment for SCA, on hematopoietic stem and progenitor cells (HSPCs). Peripheral blood mononuclear cells (PBMCs) were isolated from patients undergoing HU therapy, chronic transfusion, both treatments, and healthy donors. Flow cytometry and statistical analysis were employed to assess HU\'s effects on HSPC populations. Our findings revealed regional variations in β-globin haplotypes, with the CAR haplotype being most prevalent in the Southeast (68%), Midwest (64%), and South (74%) regions. Genotype distribution also varied regionally, and it showed to impact the association with clinical complications. Homozygous BEN patients exhibited a significant correlation with stroke, splenopathy, and osteopathy, while the presence of a single BEN allele showed a protective effect against certain complications, including death. Regarding HU treatment, it was associated with an increase in CD34+ cells, and CD34+CD235a+ cells. Notably, HU-treated patients exhibited an immunophenotypic profile for accelerated cell proliferation and differentiation in the bone marrow, potentially limiting their suitability for gene editing therapies. The molecular characterization of β-globin gene haplotypes is crucial for clinical management in SCA patients, emphasizing the importance of personalized treatment based on specific haplotypes and clinical features. Meanwhile, the second study highlights HU as a significant modulator of stress erythropoiesis and a controller of compensatory hematopoiesis. Understanding these features is vital for integrating processed HSPCs in cellular therapies, such as gene therapies, and sheds light on hematopoiesis kinetics and the complexities of human hemoglobin switching mechanisms. The results underscore the need for tailored therapeutic strategies for SCA patients based on both genetic and treatment-related factors.